(untitled) (Ius Novum, 2023)
The article is of scientific nature and undertakes research into the procedure of issuance of the European protection order by a Polish court or a public prosecutor, resulting in the execution of a protective, penal or probation measure by a competent judicial or equivalent authority in a Member State of the European Union, which requires refraining from staying in certain environments or places, and contacting or approaching certain people. The regulation concerning the execution of such an order by the competent authority of a Member State has been omitted herein. The aim of the main research theses is to show that this measure plays an important role as makes it possible to continue the protection of the aggrieved in another Member State. The research findings are original in character. They have primarily national range but can also be useful in other countries due to the fact that they relate to the EU instrument. The article analyses the essence of the European protection order, the requirements for its issuance, including the ruling on the measure of protection of the aggrieved, the necessity of the issuance of the European protection order to protect the rights of the aggrieved, the motion of the aggrieved, the European protection order issuance proceeding, in particular the authorities authorised to issue it, the form of the ruling, the forum for its issuance, the issuance mode, entitlement to appeal, the transmission of the European protection order, and information obligations. The paper is important for science because it contains an in-depth dogmatic analysis and a large load of theoretical thought, as well as for practice, as it indicates the direction of interpretation of the requirements for the application of this measure and the issuance procedure.